2015
DOI: 10.1111/aos.12665
|View full text |Cite
|
Sign up to set email alerts
|

Cataract surgery and age‐related macular degeneration. An evidence‐based update

Abstract: ABSTRACT.Purpose: Age-related macular degeneration (AMD) and cataract often coexist in patients and concerns that cataract surgery is associated with an increased risk of incidence or progression of existing AMD has been raised. This systematic review and meta-analysis is focused on presenting the evidence concerning progression of AMD in patients undergoing cataract surgery. Methods: We performed a systematic literature search in the PubMed, Medline, Cochrane Library and CINAHL databases. Two randomized trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 76 publications
3
49
0
2
Order By: Relevance
“…However, other studies have failed to detect an association between cataract surgery and AMD progression, most notably in the large Age-related Eye diseases Study (AREDS)53 and also recently in the Korean National Health and Nutrition Examination Survey (KNHANES)5455. A recent systematic review also concluded cataract surgery did not increase the risk of progression to exudative AMD56. Interesting, we only demonstrated significant association between cataract surgery with typical AMD but not with PCV.…”
Section: Discussionmentioning
confidence: 42%
“…However, other studies have failed to detect an association between cataract surgery and AMD progression, most notably in the large Age-related Eye diseases Study (AREDS)53 and also recently in the Korean National Health and Nutrition Examination Survey (KNHANES)5455. A recent systematic review also concluded cataract surgery did not increase the risk of progression to exudative AMD56. Interesting, we only demonstrated significant association between cataract surgery with typical AMD but not with PCV.…”
Section: Discussionmentioning
confidence: 42%
“…Epidemiologic data point both towards and against an association between cataract surgery and incidence and/or progression of AMD (Qian & Young 2014). A recent meta-analysis summarizing findings from epidemiologic studies found that the odds for a patient having any or early AMD was approximately doubled in patients with unoperated cataracts compared to patients without cataracts and that the odds ratio of having early or late/exudative AMD was approximately 1.5 in patients with operated cataracts compared to patients who did not have cataract surgery (Kessel et al 2015). Patients with AMD have less visual improvement after cataract surgery than patients without retinal pathologies, but nevertheless they experience an improved visual acuity up to ten years after surgery (Monestam & Lundqvist 2012), and they report an improved subjective visual function (Shuttleworth et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Faced with this lack of a strong scientific background to guide the clinicians and patients as to if and when a patient with cataract and neovascular AMD should be offered cataract surgery (Jonas et al 2007;Kessel et al 2015), we decided to review all hospital files of patients receiving anti-VEGF treatment for neovascular AMD who had been operated for cataract while in anti-VEGF therapy. The aim of the study was to evaluate the changes in visual acuity after cataract surgery and to compare the need for intravitreal injections in the time periods before and after cataract surgery.…”
Section: Introductionmentioning
confidence: 99%
“…A systemic screening and meta-analysis published by Kessel et al in 2015 evaluated previous publications investigating the ratio of progression, as well as conversion to the exudative type, among ARMD cases after cataract surgery. 11 Based on the results of their study, they declared that cataract surgery had a positive effect on the cases' functional vision, and that the surgery did not increase the risk of ARMD progression. The use of telescopic IOL instead of standard IOLs following surgery has already been previously evaluated among ARMD cases with planned cataract surgeries.…”
Section: Discussionmentioning
confidence: 99%